Права дитини у концепції соціального виховання в УСРР - Повар, О.; Povar, O. (Східноєвропейський національний університет імені Лесі Українки, 2016)
В УСРР в 1920-ті роки на відміну від освітньої системи РСФРР, де центральним моментом була трудова школа, центр ваги було зміщене в бік соціального виховання, завдяки цілої низки факторів. Крім того, УСРР була єдиною республікою СРСР, де було прийнято Кодекс законів про освіту, який діяв майже до 1970-х років.The article analyzes the origins of the idea of children's rights of Ukraine in the national philosophical and pedagogical science of the 1920-ies with a focus on the Declaration on Social Education of Children and the ideas of its authors (A. Popov, G. Grynko, J. Mamontov). The theory was corroborated as part of a plan for a communist transformation of the society and determined the principles of the Ukrainian SSR policy in the domain of education aimed at bringing up children in the spirit of communism through the concepts of labor education. At the same time the Declaration put forward the idea of children's rights, namely, it suggested to register all children aged from 7 to 15; to use all means to ensure the rights of every child to education, material security, upbringing, health, pedagogical (rather than purely legal) influence on the offenders; to remove the child from the street, and to protect the rights of children, who live in a family but need certain kind of support. It is shown that the Declaration is based on pre-revolutionary philosophical, legal and pedagogical ideas of the Russian philosophers and educators. It was for the first time in the history of Ukraine that the child's legal status as a separate legal entity had been defined.
Children’s Rights in the Paradigm of Social Education in the Ukrainian SSR
Keywords: права дитини; Соціальне виховання; Декларація про соціальне виховання дітей УСРР; Кодекс законів про народну освіту; трудова школа; дитячи будинки; Г. Гринько; Я. Ряппо; О. Попов; children's rights; social education; social education Declaration of the Ukrainian SSR children; Code of Laws on public education; labor school; orphanages